hey everyone anyone know the answer for this question?
Attachments:
![](https://hi-static.z-dn.net/files/d64/d6164e4a118474c0c0336bc8f0740099.jpg)
Answers
Answered by
1
as x + 3 = 7
therefore x = 7- 3 = 4
therefore -5x + 12 = -5(4) +12
= -20 + 12
= -8
so the answer is -8 not 4
PLEASE MARK AS BRAINLIEST
Answered by
1
Answer:
The answer is not 4, it is -8
Step-by-step explanation:
x = 7 - 3 = 4
-5x = -20
(-5x + 12) = (-20 + 12) = -8
Hope it helps, if you have other questions, please ask...
Similar questions